Therapy-Related Myeloid Neoplasm in Non-Hodgkin Lymphoma Survivors - Bari, Alessia (Università Cattolica del Sacro Cuore, 2011)
Relatively little data on secondary cancers is available regarding patients treated for non-Hodgkin lymphoma (NHL), compared with those treated for Hodgkin lymphoma. Evolving treatment regimens have improved survival outcomes for NHL patients. As a result of this improvement, secondary malignancies are becoming an important issue in NHL survivors. This review aims to report data on this topic previously published by our group, adding unpublished results from the Modena Cancer Registry (MCR). We recently performed four studies about secondary neoplasms in NHL survivors: two studies analysing the risk of secondary neoplasms in patients treated for indolent and aggressive NHL; a meta-analysis of 23 studies investigating the risk of secondary malignant neoplasm (SMN) after NHL treatment; and a still-unpublished study evaluating the incidence of therapy-related myeloid neoplasm (t-MN) in patients treated for NHL (from the MCR database). The first two studies analysed 563 patients with indolent NHL and 1280 patients with diffuse large B-cell lymphoma (DLBCL) enrolled in the Gruppo Italiano Studio Linfomi (GISL) trials. Results showed that the cumulative incidence of secondary tumours was 10.5% at 12 years for indolent NHL and 8.2% at 15 years for DLBCL. Results of the meta-analysis indicated that NHL patients experienced a 1.88-fold increased risk for SMN compared with the general population; the standardized incidence risk (SIR) for secondary acute myeloid leukaemia (AML) was 11.07. Based on data from the MCR from 2000 through 2008, we found that the SIR was 1.63 for developing a secondary malignancy after NHL, and 1.99 for developing secondary haematological malignancies. Regarding myelodysplastic syndrome and/or AML incidence, nine NHL patients developed t-MN with a higher risk than expected (SIR 8.8, 95% CI: 4.0–16.6). In conclusion, patients treated for NHL are at increased risk of developing SMN. Regarding t-MN, data from the meta-analysis and the MCR demonstrate an excessive risk of developing AML (SIR 11.07 and 5.7, respectively) compared with solid SMN after treatment for NHL. Thus long-term monitoring should be considered for NHL survivors.